Multiphysics analysis of heat pipe cooled microreactor core with adjusted heat sink temperature for thermal stress reduction using OpenFOAM coupled with neutronics and heat pipe code - Jeong, Myung Jin; Im, Jaeuk; Lee, San; Cho, Hyoung Kyu (Frontiers in Energy Research, 2023)
Heat-pipe-cooled microreactors (HPRs) have advantages such as a compact design, easy transportation, and improved system reliability and stability. The core of an HPR consists of fuel rods and heat pipes in a monolith, which is a solid block structure containing many holes for the fuel rods and heat pipes. When designing the core of an HPR, high thermal stress and reactivity feedback owing to thermal expansion are important considerations. Therefore, a high-fidelity multiphysics analysis tool is required for accurately analyzing an HPR core. When performing a multiphysics analysis, it is necessary to couple the heat pipe thermal analysis code, thermal-structural analysis code, and neutronics code. To develop a multiphysics analysis tool, OpenFOAM, an open source Computational Fluid Dynamics (CFD) tool, and ANLHTP, a heat pipe thermal analysis code, were coupled. In this process, the structural analysis solver of OpenFOAM was verified, and its limitations were improved. To confirm the proper working of the code, the mini-core problem was analyzed using the OpenFOAM-ANLHTP coupled code. Next, to consider the reactivity feedback, coupling with PRAGMA, a GPU-based continuous-energy-Monte Carlo neutronics code was performed, and the multiphysics analysis capability of the OpenFOAM-ANLHTP-PRAGMA coupled code was confirmed through an analysis of the MegaPower reactor core. To reduce the temperature distribution within the monolith, the temperature distribution of the heat pipe sink was adjusted, and the reduced thermal stress of an HPR core was observed.